The Role of Guardianship in Inheritance Law: Protecting Vulnerable Heirs - Ion, Gabriel Florinel; Pusca, Andy (Acta Universitatis Danubius. Juridica, 2024)
The article examines in depth the crucial role of the guardianship institution in succession law, with a particular focus on the protection of vulnerable heirs such as minors and persons with disabilities. In the first part, the definitions and historical evolution of guardianship are presented, together with analyzes of typologies, such as legal, voluntary and temporary guardianship. Also, there are the legal procedures required for the appointment of a guardian, emphasizing the essential criteria and his responsibilities. The chapter on the rights and obligations of the guardian includes aspects of the administration of the inherited property and the welfare of the heir. A particular focus is given to safeguards for vulnerable heirs, as well as specific challenges such as abuse of power, conflicts of interest and risks of negligence. The article also includes jurisprudential analysis, illustrating practical problems and solutions in guardianship enforcement. In conclusion, recommendations are made to make existing legislation and practices adapt to the special needs of vulnerable heirs and the current complexes in inheritance law.